2022
DOI: 10.21203/rs.3.rs-1769637/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Beneficiary of bone marrow-derived mesenchymal stem cells primed with oestradiol in alleviating collagen-induced arthritis​

Abstract: This study was conducted to investigate the effects of the oestradiol (ES)pulsed bone marrow-derived mesenchymal stem cell (BM-MSC) to treat adjuvant-induced arthritis in Wistar rats. BM-MSCs were pulsed with ES (0, 10,100 and 1000 nM) for 24 hours. RA induced collagen and Freund's Complete Adjuvant into the base of the tail of Wistar rats. In vitro results showed that the least effective concentration of ES that can promote potent anti-inflammatory properties in the MSC population is 100 nM. At this concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…In another study, the dosages of 17β-estradiol used were 10, 50, 100, 500, 1, 10, and 50 mM [47]. The least effective concentration of 17β-estradiol that could promote potent anti-inflammatory properties in the mesenchymal stem cell population was 100 nM [48]. Lower concentrations (0.01 and 1 nM) appeared to promote RUNX2 expression, but higher quantities of the drug (1 and 10 nM) decreased the expression.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the dosages of 17β-estradiol used were 10, 50, 100, 500, 1, 10, and 50 mM [47]. The least effective concentration of 17β-estradiol that could promote potent anti-inflammatory properties in the mesenchymal stem cell population was 100 nM [48]. Lower concentrations (0.01 and 1 nM) appeared to promote RUNX2 expression, but higher quantities of the drug (1 and 10 nM) decreased the expression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CC can treat a variety of arthritis, and it is better for OA, RA and GA. CC has the characteristics of multiple components, multiple targets, and multiple pathways in the treatment of arthritis. Currently, IL-10, IL-1β, IL-6, MMP-3, TNF-α and other targets have been verified to play a role in treating arthritis by CC ( Table 2 ) ( Sun et al, 2011 ; Yuan et al, 2014 ; Kienhorst et al, 2015 ; Huang et al, 2019 ; Thomas, 2020 ; Che et al, 2021 ; Li et al, 2021 ; Wu et al, 2021 ; Arra et al, 2022 ; Zhang et al, 2022 ; Cao et al, 2022 ; Du et al, 2022 ; Pacifici, 2022 ; Wirth et al, 2022 ; Xiao et al, 2022 ; Yang et al, 2022 ; Sun et al, 2023a ; Barbarroja et al, 2023 ; Li et al, 2023 ; Brix et al, 2023 ; Wang et al, 2023b ; Wang et al, 2023 ; Ghosh et al, 2023 ; González-Chávez et al, 2023 ; Hecquet et al, 2023 ; Jahantigh et al, 2023 ; Ji et al, 2023 ; La Bella et al, 2023 ; Leung et al, 2023 ; Lin et al, 2023 ; Luo et al, 2023 ; Zeng et al, 2023 ; Zhang et al, 2023 ). However, the types of arthritis treated with these targets are not completely clear.…”
Section: Deep Exploration Based On Potential Therapeutic Targets For ...mentioning
confidence: 99%